DISCLOSURE DUTIES IN INSURANCE CONTRACT - Ivancevic, Katarina B (Pravni zapisi, 2021)
In this paper, the author considers issues related to the pre-contractual obligation of the insurance policyholder to report to the insurer circumstances significant for the risk assessment. The aim of this paper is to compare the provisions of the The Law on Contract and Torts (LCT), proposals for changes in Serbian law envisaged in the Preliminary Draft of the Civil Code of the Republic of Serbia with solutions from comparative law and the provisions of the Principles of European Insurance Contract Law (PEICL). The analysis showed that it is necessary to update the solutions from the LCT and that the proposed changes, in terms of special rules regarding the obligation to report circumstances relevant to risk assessment to the insurer, are largely in line with modern solutions in comparative law and PEICL. The author points out that the proposed solutions can be supplemented and improved.
Keywords: disclosure duty; risk; precontractual duty; circumstances; insurance; breach; sanctions